(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
the article analyzes the improvement of operational processes by ensuring the safety of work in production. The problem raised in the research: how to ensure work safety by improving the company's operational processes in production? The object of work is the possibilities of improving operational processes by ensuring work safety. The aim of the work is to analyze the possibilities of improving operational processes by ensuring work safety in production. Job objectives: to analyze the possibilities of improving operational processes by ensuring work safety from a theoretical aspect; to investigate the possibilities of improving operational processes by ensuring work safety in the production company; prepare a plan for the improvement of operational processes by ensuring work safety in production. Research methods: analysis of scientific literature and other informational sources; data collection and systematization method; descriptive analysis method used to report research data; the summarization method is used to evaluate the results of the analysis; the research uses data analysis and observation method.After conducting the research and analyzing the measures applied in the operational processes, ensuring the safety of work in production, a plan for improving the operational processes was prepared and presented, which offers specific measures for increasing the efficiency of the processes and reducing the risk of accidents. The measures implementation plan is designed to solve existing problems in the company's operational processes, offering recommendations on how to reduce or completely eliminate accidents by ensuring work safety. The proposed plan will help minimize the risk of accidents at work by ensuring work safety in operational processes. The created plan for improving operational processes with measures by ensuring work safety and reducing the risk of accidents at work is universal and can be applied in other manufacturing companies that seek to improve operational processes by ensuring work safety